Contribution of EU structural funds assistance to the development of economic environment through collaboration of business and science in Latvia - Meženiece, Marta; Rivža, Baiba (Business, Management and Economics Engineering, 2011)
The article analyses the good practice of Finland, which reconstructed the path changing towards building innovation-based economy, and Denmark, where the several programmes for network building and enhancement of collaboration between entrepreneurs as well as entrepreneurs and research institutes were introduced successfully, in order to make recomendations for development of economic environment in Latvia. The authors consider, that in the case of Latvia, at first, the government must take action in order to establish the macro-level environment that enables conditions for innovative self-renewing systems as well as introduce schemes that would facilitate knowledge spillover and commercialization, promote business activities of academic staff and researchers, as well as formation of networks and clusters.